2015
DOI: 10.3233/jhd-150164
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Validity of the Short Version of the Problem Behaviours Assessment (PBA-s) for Huntington’s disease: A Rasch Analysis

Abstract: 240 words Manuscript: 5017 wordsManuscript Reference Number: 15-164 (1 st revised submission) All authors have contributed the work, agree with the presented findings, the work has not been published before nor is being considered for publication in another journal. Correspondence address

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…improved PBA-s validity. 26 In our study, scores of 1 (slightly present, questionable) and 2 (mild or present but not a problem) were combined to reflect mild symptoms and scores of 3 (moderate, symptom causing problem) and 4 (severe or almost intolerable) were considered severe symptoms. By taking the percentage of individuals who had a severity score of 0 for each behavioral symptom and subtracting it from 1, the frequency at which all symptoms were experienced, irrespective of severity, was determined.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…improved PBA-s validity. 26 In our study, scores of 1 (slightly present, questionable) and 2 (mild or present but not a problem) were combined to reflect mild symptoms and scores of 3 (moderate, symptom causing problem) and 4 (severe or almost intolerable) were considered severe symptoms. By taking the percentage of individuals who had a severity score of 0 for each behavioral symptom and subtracting it from 1, the frequency at which all symptoms were experienced, irrespective of severity, was determined.…”
Section: Discussionmentioning
confidence: 97%
“…The PBA-s offers a reliable assessment of behavioral symptoms with an estimated interrater reliability of 0.82 (95% CI = 0.65-1.00) for severity scores and 0.73 (95% CI = 0.47-1.00) for frequency scores. [24][25][26] A wide range of behavioral symptoms were reported by most subjects by the time of ENROLL-HD matriculation with apathy, anxiety, irritability and depression reported most frequently. Previous studies have also found apathy to be the most common behavioral symptom over the course of HD, with depression and irritability also common.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, higher scores in TMT B-A and Stroop interference indicate worse performance, while for verbal fluency and SDMT poorer performance corresponds to lower scores. Psychiatric measures included the Depression and Anxiety subscales of the short version of the Problem Behavioural Assessment (PBA-s (McNally et al, 2015)), multiplying frequency by severity, with higher scores indicating more severe symptoms, as well as the Spanish version of the sensitivity to punishment and sensitivity to reward questionnaire (SPSRQ (Torrubia et al, 2001)), with higher scores indicating more sensitivity, and the short Lille apathy scale (Sockeel et al, 2006), with higher scores indicating more severity. Due to time constrains, some of the behavioural variables were not acquired in some participants.…”
Section: Methodsmentioning
confidence: 99%
“…In our opinion, these cases are not equal; hypothesis is that it is more likely that severity – rather than frequency – of apathy is related to the neurodegenerative process in HD. McNally et al ( McNally et al, 2015 ) have also pointed out in their re-evaluation of the PBA-s that using the product score might statistically not be appropriate as it is not a ratio scale. For future research, it would be of interest to further evaluate the use of the different PBA-s scores.…”
Section: Discussionmentioning
confidence: 99%